Photocatalytic inactivation of E. Coli by ZnO–Ag nanoparticles under solar radiation. Issue 63 (10th July 2015) - Adhikari, Sangeeta; Banerjee, Aditi; Eswar, Neerugatti KrishnaRao; Sarkar, Debasish; Madras, Giridhar
<x xml:space="preserve">Abstract</x> Porous and fluffy ZnO photocatalysts were successfully prepared via simple solution based combustion synthesis method for effective E. Coli inactivation.